A Study on Prevalence and Molecular Characterization of Spike Protein of SARS-COV2 in Pakistan - Mahnoor Rizwan; Abdul Ahad; Sadia Aziz; Nazir Ahmed Lone; Tabasum Naz; Muhammad Bilal Khan; Laila Jafri; Liaqat Ali (Life and Science)
Objective: To examine the prevalence of antibody IgG/IgM and designing follow-up study of six months and to perform the molecular characterization and sequence analysis of spike protein of SARS-CoV-2. Study Design: Prevalence study. Place and Duration of the Study: The study was conducted in the Post-Graduate Lab of the National University of Medical Sciences (NUMS) Rawalpindi, Pakistan from January 2021 to June 2021. Methods: 112 suspected patients with mild and severe symptoms were tested by PCR (polymerase chain reaction) and all were positive. Antibody profiling of vaccinated and non-vaccinated patients was performed by enzyme-linked immunosorbent assay (ELISA) and followed up for up to six months. Results: Ten patients were identified as re-infected and were subsequently re-tested via PCR and DNA sequencing. The IgG/IgM of immunized patients was 11.87IU/mL and 3.87IU/mL in non-immunized individuals. Genomic analysis indicated that all the sequences belong to delta variant (21A and 21J sub-lineages). Mutations were observed in spike protein at I1169V, D950N in 21A and T951I and S254F in 21J sub-lineages. Conclusion: This study revealed the significance of measuring antibody levels among vaccinated and unvaccinated individuals. Additionally, mutations in the spike gene of the delta variant of SARS-CoV2 can influence the pathogen's mutation rate, leading to changes in its transmissibility and pathogenicity.